Electrical Design of a Portable Pure Sine Wave Inverter Using Ferrite Core Transformer and Double Stage Technique - Kunnu Purwanto; Aditya Agus Wijayanto; Yudhi Ardiyanto; Karisma Trinanda Putra (Universitas Muhammadiyah Yogyakarta, 2023)
The size of the iron core transformer in an inverter is large and heavy because it has more conductor turns and works at low frequencies. In contrast, ferrite core transformers are designed to work at high frequencies, so the number of turns of the conductor is less, and the transformer size is relatively small and light. Device portability is a significant challenge in designing high-power inverters. This research uses a ferrite core transformer to design a portable pure sine wave inverter. A two-stage technique is proposed in designing the inverter so that the dc-link voltage and capacitor size can be flexibly selected, and the device size can be compacted. The design consists of two stages. First, a circuit to generate a 400-Volt DC voltage is designed using IC SG3525, a MOSFET power amplifier, and a ferrite core step-up transformer. Second, a pure sine wave generator circuit is constructed using an EGS002 module, MOSFETs, and a filter circuit. Experiments are performed by measuring the output voltage, monitoring power and frequency, and observing the waveform with an oscilloscope. The results reveal that the designed inverter can generate a 220-volt pure sine wave output, a maximum power of 500 Watts, a frequency of 50 Hz, and an efficiency between 91.4% to 98.1%.